An Improved Approximation for DIPPR-Based Predicting Speed of Sound in Long-Chained n-Alkanes - POSTNIKOV, Eugene B.; NEDYALKOV, Yuriy V.; POLISHUK, Ilya (Archives of Acoustics, 2018)
IIn this short communication, we revise a correlation for the saturated liquid isothermal compressibility based on the data available in DIPPR (Postnikov, 2016) which considers the molecular non-sphericity and addresses a problem of predicting speeds of sound in saturated long-chained alkanes. In addition, we correct a misprint appeared in the cited work and provide programming code used for the realisation of the proposed calculations.